Peran Pupuk Eco Farming dan Vermikompos Terhadap Pertumbuhan Cabai Merah - Siti Khairani; Lily Novianty; Juhardi Sembiring; Denny Mukhlisin (Agrosains : Jurnal Penelitian Agronomi, 2022)
Eco farming fertilizers and vermicompost are very important in plant cultivation because they can affect plant growth. Various methods began to be developed in order to create quality organic fertilizers so that red chili plants grow well. The purpose of this study was to determine whether or not the effect of the eco farming fertilizers and vermicompost on red chili plant growth, knowing the right dose of eco farming fertilizer on red chili plants, and knowing the interaction between eco farming fertilizers and vermicompost on red chili plant growth. The method used was Factorial Random Block Design with 2 factors, provision of vermicompost (V) consist of 3 levels, namely V0 (0 g/polybag), V1 (25 g/polybag), and V2 (50 g/polybag). Eco farming fertilizer consists of 3 levels, namely E0 (0 ml mixed fertilizer/polybag), E1 (25 ml mixed starter/polybag), and E2 (50 ml mixed starter/polybag). Parameters observed were plant height (cm), stem diameter (mm) and root volume (ml). The result showed that the effect of vermicompost fertilizer and eco farming on the growth of red chili has no significant effect on plant height, stem diameter and root volume. The best dose was seen from the observation of plant height parameters, stem diameter and root volume when giving 25% vermicompost and 50 ml eco farming fertilizer on red chili. The interaction of vermicompost fertilizer and eco farming on the growth of red chili gave no significant effect on plant height, stem diameter and root volume.